"See One, Do One, Teach One, Have One": A Novel Variation on Regional Anesthesia Training. Issue 5 (1st September 2002) - McDonald, Susan B.; Thompson, Gale E.
Abstract : Introduction: Is it possible to determine the number of nerve blocks needed for residents to become competent in regional anesthesia? Several studies have focused on this question, and the Residency Review Committee (RRC) for Anesthesiology has now defined a "minimum clinical experience" for some aspects of regional anesthesia training. In our experience, personally being a regional block recipient can also serve to enhance training. Methods: Many residents at Virginia Mason Medical Center have received regional anesthetics as volunteers in research projects. We designed questionnaires to define their perceptions in both performing and receiving regional anesthesia. Results: Twenty-one residents were recipients of a total of 72 regional anesthetic procedures. Many residents' comments focused on the discomfort of local anesthesia infiltration, the value of sedation, a better appreciation of the patients' perspectives, and improved preoperative consultation. Residents experiencing paresthesias were more likely to consider paresthesias as bad ( P = .0098). Conclusion: The lessons learned from personally receiving a regional anesthetic are invaluable and can improve the quality of training, as well as the relationship between anesthesiologist and patient.